Mengukur Kesiapan Guru Selama Pelaksanaan Hybrid Learning di SD Strada Van Lith II - Clara Anugrah Barus; Muh Asdar; Veronica Ari Nugroho Rini; Samuel Lukas (FKIP, Universitas Palangka Raya, 2023)
Online education is growing rapidly due to the Covid 19 pandemic. For almost three years this pandemic is still ongoing, so the world of education has also begun to transform and innovate to be able to provide the best service for students and teachers. Currently, many schools have started to use technology in learning, one of which is using hybrid learning. Thus, teacher readiness is an important aspect in dealing with any changes or new situations. Especially in an era like this, it is very important for us to be able to see the extent to which teachers are prepared to deal with it. Various scales for measuring teacher readiness have been developed, one of which is the Teacher Readiness for Online Learning Measure (TROLM) Communication self-efficacy (CSE), Institutional support (IS), Self-directed learning (SDL) scale, Learning transfer self-efficacy (LTSE). The researcher used a sample of 19 SD Strada Van Lith II teachers with the Non-Probability Sampling technique. Questionnaires were distributed to all respondents via google form in the hope of getting results that answered the research objectives by using a Likert scale to minimize errors. The results of this study found that the teacher's overall readiness had an effect on the implementation of hybrid learning by utilizing technology